Professional and personal impact of the COVID-19 pandemic restrictions on non-COVID-19-related clinical research - Ann J. Melvin; Pooja Tandon; Carly Rowe; Denae Clohessy; Tonya M. Palermo (Journal of Clinical and Translational Science, 2021)
The COVID-19 pandemic has led to major disruptions in the clinical research enterprise. Investigators and staff at the University of Washington and Seattle Children’s Research Institute (SCRI) were surveyed to determine the impact of the pandemic restrictions on their non-COVID-19 clinical research studies. Enrollment and study visits were stopped for over half of the interventional trials. There were both positive and negative impacts of the work restrictions on the professional and personal lives of faculty and staff. Academic and research institutions should consider how best to support investigators and their teams during this pandemic.